UNREAL ENGINE 5 CHARACTER CREATION, ANIMATION AND CINEMATICS : create custom 3D assets and bring them to life in Unreal Engine 5 using MetaHuman, Lumen, and Nanite - VENTER, HENK (PACKT PUBLISHING LIMITED, 2022)
Get to grips with the base workflow and create your own cinematic scenes in UE5 by learning to develop the main elements, animate, and combine them into a complete rendered movie scene with the help of key images printed in color Key Features Perform your entire rigging and animation workflow inside Unreal Engine 5 using Control Rig tools Create hand-keyed animations and clean up motion capture natively in Unreal Engine Learn the basics of creating 3D assets and customizing a MetaHuman for your movie needs Book Description Unreal Engine 5 (UE5) offers beginners and seasoned professionals the ability to create detailed movie scenes with realistic human characters using MetaHuman and combine it with custom props and environments. It also comes with built-in industry standard animation tools to develop such scenes in a fraction of the time compared to old methods. This book takes you through the entire 3D movie production pipeline using free (open - source) software. By following the step-by-step, beginner-friendly tutorials in this book, you'll learn how to create your own custom 3D assets in Blender and texture these 3D assets in Quixel Mixer. Next, you'll take these completed 3D assets into Unreal Engine 5 and use them to build a virtual 3D movie set for your 3D movie. You'll also populate your 3D movie set by using Quixel MegaScans assets and create and customize your own photorealistic human character using MetaHuman Creator and UE5. As you advance, you'll discover how to rig, skin, and animate these 3D assets and characters using Blender and UE5's new Control Rig. Finally, you'll explore the process of setting up your movie cameras and animation sequences and rendering your 3D movie using UE5's Sequencer. By the end of this Unreal Engine book, you'll have learned how to combine different elements in UE5 to make your own movies and cinematics. What you will learn Create, customize, and use a MetaHuman in a cinematic scene in UE5 Model and texture custom 3D assets for your movie using Blender and Quixel Mixer Use Nanite with Quixel Megascans assets to build 3D movie sets Rig and animate characters and 3D assets inside UE5 using Control Rig tools Combine your 3D assets in Sequencer, include the final effects, and render out a high-quality movie scene Light your 3D movie set using Lumen lighting in UE5 Who this book is for This book is for beginners to Unreal Engine or 3D animation and art in general who want to learn the entire process of creating 3D movies with Unreal Engine 5. Experienced 3D artists and animators new to UE5 will also find this book invaluable as it covers cutting-edge techniques for making real-time 3D movies using Unreal Engine, Blender, Quixel Mixer, and Quixel Bridge. Although prior experience with 3D software is not necessary, it will be helpful in understanding the concepts more easily.